Vicissitudes of the social role in the context of the contemporary society - Acuña, Eduardo; Sanfuentes, Matías (Revista de Psicología, 2006)
Results of a group activity developed to study contemporary society from a psychoanalytic point of view are presented. The theoretical and metho dological aspects that support this activity are based upon a tradition that focuses on the exploration of group and organization’s dynamics. Results drawn from the application of the method in 2005 and 2006 in different countries, including Chile, are described. A central discovery shows that societies around the world are affecred by very profound changes thar generate grear levels of anxiety and a whole range of disturbance in people`s daily life. Anxiety mobilises different forms of defence mechanisms, which generate conflicts that hinder individuals`participation in society processes.